Pengaruh Penambahan Latihan Core Stability Terhadap Peningkatan Nilai Kesegaran Jasmani B Pada Prajurit - Tjetjep Sudrajat; Wita Hana Puspita (CV RIFAINSTITUT, 2021)
An Army soldier must be able to foster physical fitness so that his body becomes healthy and can carry out his main duties to maintain the sovereignty and territorial integrity of the Republic of Indonesia. This study aims to determine the effect of adding core stability exercise to increasing the value of physical fitness B in soldiers. Quasi experimental design research held at Yon Armed 4 Cimahi. A sample of 20 soldiers divided into 2 groups. The dependent variable is the physical fitness score B and the independent variable is the core stability exercise. Exercise is carried out for 4 weeks with a frequency of 3 times per week. The difference in test results between the experimental group and the control group both before and after core stability exercise was tested by independent T test. There was a difference in the mean physical fitness scores between the experimental group (Mean= 85.80; SD= 2.82) and the control group (Mean= 82.50; SD= 2.32) before the intervention, and the difference was statistically significant (p= 0.011). There was a difference in physical fitness scores before and after the intervention between the experimental group (Mean= 3.90; SD= 1.52) and the control group (Mean= 1.60; SD= 0.70) and statistically significant (p < 0.001), with effect size = 1.94. Conclusion core stability exercise is effective to increase the physical fitness value of B on soldiers of Yon Armed 4 Cimahi